Making a difference to the milk business in Kenya - WRENmedia (WRENMedia, 2010)
In Kenya, Margaret Wambugu explains how Kenya's small scale milk vendors have improved handling and hygiene of milk, raised their profit margins and increased milk supplies to consumers at home or in milk bars. This progress in the milk supply chain contributes US$33 million annually to the Kenyan economy.